Two rare cases of severe community-acquired bloodstream infections: a clinical case report - Meng, Li-Na; Li, Gang (Frontiers in Immunology, 2024)
BackgroundThe escalating demographic shift towards an aging population and the widespread occurrence of immunological diseases have contributed to an elevation in the frequency of community-acquired infections. Notably, among these infections, community-acquired bloodstream infections (CABSI) stand out due to their significant lethality. Detailed medical history inquiries, assessment of underlying immune status, detection of the source of infection, and initial precise identification and treatment of the infectious agents can improve the prognosis of CABSI.Case descriptionIn this paper, two incidences of severe CABSI with insidious onset and rapid progression are described. Both patients had compromised basic immunity: one developed the infection following unhygienic dietary practices, and the other after repeated enemas leading to intestinal damage. Blood genomic sequencing revealed the presence of Klebsiella pneumoniae and Staphylococcus aureus in the respective cases, with the origin of the infection traced back to the gastrointestinal tract. Both patients experienced positive outcomes following targeted antibiotic therapy, fluid resuscitation, support for organ function, and surgical interventions. Nevertheless, one patient manifested dry gangrene in the extremities during the course of treatment, potentially associated with the administration of vasoconstrictor drugs, considering the compromised baseline vascular conditions.ConclusionClinicians are advised to expeditiously uncover concealed medical histories and potential sources of infection in patients, thoroughly investigate the origin of the infection, and initiate early genomic testing to ascertain the specific nature of the infection. This proactive approach aims to facilitate precise treatment strategies and, consequently, enhance the overall prognosis.